Eagle down - Bowen, Carl (Bowen, Carl. Shadow Squadron., 2013)
Sergeant Edgar Brighton of the Shadow Squadron is in Colombia, assisting on an anti-drug operation--but when he is captured and tortured by the rebels he must find a way to escape before they break him.